Diagnostic Consultations: a Speech-Act Theoretical Reconstruction for the Design of Consultation Systems - Müller-Kolck, U. (Methods of Information in Medicine, 1991)
In this paper the theory of speech acts is applied for a structural reconstruction of medical diagnostic consultations. The reconstruction provides the conceptual model for a research prototype of a consultation tool which is expected to play a mediating role between the participants in the professional diagnostic discourse. Preliminary results of the design will be outlined.
Keywords: Diagnostic Consultation Systems; Medical Diagnosis; Speech Acts; Application Modeling